SINGING ACTIVITIES IN LEARNING MATHEMATICS ON LENGTH AND HEIGHT UNITS MATERIAL IN CLASS III A SDN 12 BANDA ACEH - Sylvia, Putri Diana; Yamin, M.; Vitoria, Linda (Elementary Education Research, 2024)
This research discusses singing activities in mathematics learning on length and weight units in Class III A SDN 12 Banda Aceh. This research aims (1) To determine singing activities in mathematics learning on length and weight unit material in class III A SDN 12 Banda Aceh. (2) To determine learning outcomes in singing activities in mathematics learning in length and weight units in class III A SDN 12 Banda Aceh. The method used in this research is descriptive qualitative. The subjects of this research were 18 students in class III A at SDN 12 Banda Aceh. Data collection techniques in this research are observation and tests. The assessment indicators in this research are if students are able to convert units of length, solve everyday problems regarding units of length, convert units of weight, solve everyday problems regarding units of weight. The results of the research show that the singing activity in mathematics learning on length and weight unit material in Class III A SDN 12 Banda Aceh was declared successful with an average student learning outcome score of 78.76 and included in the good category. The results of the initial test (pre-test) showed a very low level of learning completeness, namely only 16.67%. However, after participating in learning with singing activities, there was an increase to 88.89% in the post-test. The class average on the post-test was 78.61, indicating an increase from the initial average of 33.88. Based on these data, it can be concluded that singing activities in mathematics learning can improve students' understanding of length and weight units in Class III A SDN 12 Banda Aceh.